Influence of internal social capital and external social capital on acquired knowledge - Linh, Nguyen Hong; Yen, Le Thi Hong; Hieu, Pham Van; Huong, Nguyen Thi Thu; Phuong, Mai Quynh (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to present a thorough empirical analysis of the impact of both internal and external social capital on the knowledge acquisition of logistics companies in Hanoi and the surrounding provinces. Using the ideas from earlier research, the study investigates the internal and external social capital as well as the knowledge that logistics companies in Hanoi and the surrounding provinces have acquired. We employed primary data from a survey of 300 workers at logistics companies in Hanoi and nearby provinces in 2023–2024. A total of 245 valid survey questionnaires were used in the analysis, which included regression modeling, EFA analysis, and reliability analysis of scales (Cronbach’s alpha coefficient). Our findings suggest that external social capital, internal social capital, and the acquisition of knowledge by logistics firms are highly valued. Internal social capital has a positive influence on knowledge acquisition by logistics firms, but we did not find that external social capital affects knowledge acquisition by logistics firms. Based on the research findings, our study emphasizes that external social capital, internal social capital, and the acquisition of knowledge by logistics firms need urgent improvement to support their business performance.